Hambatan Kontraktor Dalam Penerapan Konsep Green Construction Di Surabaya: Barriers’s Contractors In Implementing The Green Construction Concept In Surabaya - Alrizal, Fahmi Firdaus; Untari, Alda Rizma; Kurniawan, Adhitya Bangkit; Kalammolah, Moch. (Media Ilmiah Teknik Sipil, 2024)
The level of carbon dioxide or global warming continues to increase in the world. It becomes one of the strongest reasons for providers of construction goods and services to apply the concept of green construction. The application of the green construction concept is still a new thing, and not all components of the green construction concept have been well implemented by contractors. In applying the concept, several obstacles have occurred. This study identified the most dominant obstacles experienced by contractors in implementing the green construction concept, especially in Surabaya. Primary data were collected and then processed through the interpretive structural modeling method to find the most dominant obstacles. Twelve obstacles spread over five levels were found in this research, namely: lack of best practices and lessons learned, lack of understanding of green construction, difficulty in getting certificates, lack of awareness of the green construction benefits, feeling no need to implement green construction, no guidelines, procedural constraints, lack of government socialization, limited availability of green land, lack of alternative materials, limited availability of environmentally friendly materials, and difficulty in obtaining environmentally friendly materials. According to the respondents, the most dominant obstacles included the absence of a guideline and the lack of socialization from the government.